Examination of Da'wah Communications on the Instagram @fuadhnaim Utilising Roland Barthes' Semiotic Framework - Ramadhani, Suci; Siregar, Amran Pikal; Sitorus, Ari Oldwin; Ginting, Abdul Fikri; Sikumbang, Ahmad Tamrin (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2024)
This study examines the application of Roland Barthes' semiotic theory in the analysis of da'wah messages disseminated through the social media platform Instagram. This research involved analyzing content posted by the @fuadhnaim account from January to October 2024. The research seeks to elucidate the denotative, connotative, and mythological significances embedded in reel-shaped preaching messages, while also examining the utilization of visual and verbal symbols to communicate Islamic ideals in the digital age. The employed methodology is descriptive qualitative, utilizing content analysis as the primary data collection tool. An investigation of the @fuadhnaim Instagram account revealed that the da'wah messages comprised five postings on faith, four on sharia, four pertaining to worship, and nine about morals. Certain reels also address prevalent topics and offline research articles. The da'wah themes presented encompass self-reflection, prayer, and critique of promiscuity, alongside an examination of falsehoods that expose social constructs, like the morality of "migrating children" and Islamic perspectives on soul mates. The findings indicate that Instagram is beneficial for da'wah, leveraging social trends to communicate Islamic ideals pertinently in the digital age. Penelitian ini berfokus pada penggunaan pendekatan semiotika Roland Barthes dalam menganalisis pesan-pesan dakwah yang disampaikan melalui media sosial Instagram. Studi ini dilakukan dengan mengkaji konten yang diunggah oleh akun @fuadhnaim selama periode Januari hingga Oktober 2024. Penelitian bertujuan untuk mengungkap makna denotatif, konotatif, dan mitos yang terkandung dalam pesan-pesan dakwah berbentuk reels, serta memahami bagaimana simbol-simbol visual dan verbal digunakan untuk menyampaikan nilai-nilai Islam di era digital. Metode yang digunakan adalah deskriptif kualitatif, dengan analisis konten sebagai teknik utama pengumpulan data. Berdasarkan analisis konten akun Instagram @fuadhnaim ditemukan bahwa pesan dakwah yang disampaikan mencakup lima unggahan tentang akidah, empat tentang syari'ah, empat terkait ibadah, dan sembilan mengenai akhlak. Beberapa reels juga membahas isu populer dan potongan kajian offline. Tema dakwah yang diangkat meliputi introspeksi diri, doa, serta kritik terhadap seks bebas, dengan analisis mitos yang mengungkap konstruksi sosial seperti moralitas "anak hijrah" dan pandangan Islam tentang jodoh. Temuan ini menunjukkan bahwa Instagram efektif untuk dakwah, memanfaatkan tren sosial untuk menyampaikan nilai keislaman secara relevan di era digital.